2019
DOI: 10.1002/jmri.26935
|View full text |Cite
|
Sign up to set email alerts
|

MRI cine‐tagging of cardiac‐induced motion for noninvasive staging of liver fibrosis

Abstract: Background: MR elastography is a noninvasive technique that provides high diagnostic accuracy for the staging of liver fibrosis; however, it requires external hardware and mainly assesses the right lobe. Purpose: To evaluate the diagnostic performance of MRI cine-tagging for staging fibrosis in the left liver lobe, using biopsy as the reference standard. Study Type: Institutional Review Board (IRB)-approved two-center prospective study. Population: Seventy-six patients with chronic liver disease who underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
(66 reference statements)
0
5
0
1
Order By: Relevance
“…However, in patients with fatty infiltration of the left ventricle (LV), that is, where the fat is inside the cardiac tissue, sequences such as ORI‐CSPAMM and ORI‐O‐CSPAMM could improve the cardiac motion and related parameters estimations. Moreover, a recent study has demonstrated that the strain estimated from tagged MR images is a valuable marker for staging non‐invasively liver fibrosis in non‐alcoholic fatty liver disease (NAFLD) patients 21 . As the NAFLD stages are an inflammatory process in the presence of fat, we hypothesize that the use of ORI sequences (particularly ORI‐O‐CSPAMM) can be helpful at the early stages of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in patients with fatty infiltration of the left ventricle (LV), that is, where the fat is inside the cardiac tissue, sequences such as ORI‐CSPAMM and ORI‐O‐CSPAMM could improve the cardiac motion and related parameters estimations. Moreover, a recent study has demonstrated that the strain estimated from tagged MR images is a valuable marker for staging non‐invasively liver fibrosis in non‐alcoholic fatty liver disease (NAFLD) patients 21 . As the NAFLD stages are an inflammatory process in the presence of fat, we hypothesize that the use of ORI sequences (particularly ORI‐O‐CSPAMM) can be helpful at the early stages of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent study has demonstrated that the strain estimated from tagged MR images is a valuable marker for staging non-invasively liver fibrosis in non-alcoholic fatty liver disease (NAFLD) patients. 21 As the NAFLD stages are an inflammatory process in the presence of fat, we hypothesize that the use of ORI sequences (particularly ORI-O-CSPAMM) can be helpful at the early stages of the disease. Even more, ORI-O-CSPAMM can be used in clinical protocols replacing SPAMM, which would increase the scan time of tagging grids by a factor of two instead of four as it would be done with ORI-CSPAMM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stiffness of the thymus in healthy children evaluated by MR elastography presented a mild negative correlation with age, height, and weight, which can be influenced by changes in the thymic epithelial space and the perivascular space [ 18 ]. Cine-MR feature tracking analysis can also provide information on tissue stiffness [ 8 , 19 21 ], in which tissue deformation is inversely proportional to tissue stiffness. Cardiovascular MR feature tracking to quantify myocardial strain has been reported to be associated with ventricular stiffness [ 19 ], and cardiac-induced deformation using cine-MR tagging analysis has been used to assess liver stiffness [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…La toma de una biopsia hepática sigue siendo el patrón de referencia para el diagnóstico de cirrosis que, además de estadificar el grado de fibrosis, contribuye a esclarecer su causa. 16,17…”
Section: Pielunclassified